2002
DOI: 10.1093/treephys/22.15-16.1137
|View full text |Cite
|
Sign up to set email alerts
|

Leaf chemical changes induced in Populus trichocarpa by enhanced UV-B radiation and concomitant effects on herbivory by Chrysomela scripta (Coleoptera: Chrysomelidae)

Abstract: To assess the potential impact of enhanced ultraviolet-B (UV-B) radiation over two trophic levels, we monitored key leaf chemical constituents and related changes in their concentration to dietary preference and performance of a specialist insect herbivore. Ramets of Populus trichocarpa Torr. & Gray (black cottonwood) were subjected to near zero (0X), ambient (1X) or twice ambient (2X) doses of biologically effective UV-B radiation (UV-B(BE)) in a randomized block design using either a square-wave (greenhouse)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 63 publications
2
33
1
Order By: Relevance
“…In turn, these changes had little to no effect on the predicted and actual digestibility and preference of a forb and shrub consumed by a small ruminant, the blue duiker. Our results differ in several ways to those of previous studies on the effects of UV-B radiation on plants (Ambasht and Agrawal 2003;de la Rosa et al 2001;Schnitzler et al 1997;Warren et al 2003) and studies documenting the effects of changes in plant chemistry caused by UV-B radiation in invertebrates (McCloud and Berenbaum 1999;Veteli et al 2003;Warren et al 2002). First, in many plants cell-wall components, such as fiber and lignin, respond to light intensity (Blair et al 1983).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In turn, these changes had little to no effect on the predicted and actual digestibility and preference of a forb and shrub consumed by a small ruminant, the blue duiker. Our results differ in several ways to those of previous studies on the effects of UV-B radiation on plants (Ambasht and Agrawal 2003;de la Rosa et al 2001;Schnitzler et al 1997;Warren et al 2003) and studies documenting the effects of changes in plant chemistry caused by UV-B radiation in invertebrates (McCloud and Berenbaum 1999;Veteli et al 2003;Warren et al 2002). First, in many plants cell-wall components, such as fiber and lignin, respond to light intensity (Blair et al 1983).…”
Section: Discussioncontrasting
confidence: 81%
“…The nutritional quality of food, in turn, can drive production, movements, and population dynamics (Cook et al 2004) of economically and ecologically important wild and domestic ruminants. Although recent studies have indicated that insects are affected by chemical changes induced by enhanced UV-B radiation (McCloud and Berenbaum 1999;Veteli et al 2003;Warren et al 2002), responses of mammalian herbivores to changes in food chemistry induced by enhanced UV-B radiation have rarely been studied. However, some evidence suggests that when plants have been naturally or experimentally excluded from UV-B radiation, they may be more nutritious for herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we are aware the conclusions about the effect of drought stress and its interaction with UV-B radiation exposure can be put in perspective of a greenhouse situation only, as the limitations of our controlled environmental studies are recognized. In our study, on-off lamp procedure for providing UV-B irradiation has been known to produce higher daily and seasonal UV doses than expected because there is no compensation (lamp modulation) for any reduction in incoming solar radiation during overcast and cloudy conditions, and during morning and afternoon periods (see Sullivan et al, 1994;Warren et al, 2002). Consequently, this is likely to exaggerate the UV-B response.…”
Section: Discussionmentioning
confidence: 80%
“…The activation of flavonol biosynthetic genes exhibited a reduction at 12 h, which may have been caused by the absence of the stimulus during the night or by circadian regulation. Flavonol glycosides are known to be important UV-B protective compounds (Li et al, 1993;Landry et al, 1995), and increased flavonol accumulation in leaves has been observed in poplar and other trees under elevated UV-B light (Warren et al, 2002(Warren et al, , 2003Keski-Saari et al, 2005;Turtola et al, 2005). HPLC analysis of extracts from leaves after 7 d of HL exposure revealed a large increase in total flavonol glycosides ( Fig.…”
Section: Identification Of Putative Pa Regulatory R2r3 Myb Genes In Pmentioning
confidence: 88%